FEATURES OF THE DEVELOPMENT OF NEOPLASMS AMONG CHEMICAL WORKERS - E. T. VALEYEVA; L. K. KARIMOVA; A. B. BAKIROV; G. F. MUKHAMMADIYEVA; E. R. SHAIKHLISLAMOVA (Кубанский научный медицинский вестник, 2017)
Aim. To study the impact of work environment and occupational factors on the development of neoplasms in chemical workers of the Republic of Bashkortostan.Material and Methods. Analysis of occupational cancer morbidity rate in certain chemical sectors within last 45 years was made using archive data.Results. A number of chemicals affecting workers of manufactures under discussion are carcinogens and they initiate the development of oncopathology among workers. Occupational cancer diseases in the structure of occupational diseases in diverse manufactures amount for 6,5 - 12% of cases. Main nosologic forms were leukoses, hyperkeratosis, skin blaqstoma, lung and bronchial cancer. Categories of risks for neoplasms among workers were within medium to very high (intolerable) limits.Conclusions. In the manufacturing processes of organic synthesis and fiberglass, there are a number of chemicals of carcinogenic type. A portion of occupational cancer diseases in organic synthesis manufacture amounts for 6,5%, in continuous fiberglass - 12% exceeding ten times All-Russian indicators.